(untitled) (Research, Society and Development, 2022)
The aborological study and the stimulation of physiological changes in health students. Given the scenario of working hours, there was a need to identify the existence of these rhythms of deprivation and functioning, since they can present the functioning of deprivation and the need to identify the existence of a rhythm of deprivation and functioning. Thus, the objective of the work as complications created by sleep information and how it may not work in everyday life, in the form of education and in the factor of social regulation of studies and professionals. Therefore, it is an integrative literature review, which includes articles between the years 2010 to 2021 in PubMed, Google Scholar and ScienseDirect databases. The results indicate that students in the health area have a significant tendency to suffer from a hormonal change, such as cortisol and melatonin, which are responsible for elaborating the programming of the biological clock, which influences social and growing dysfunctions. susceptibility to obesity, depression and anxiety. As a result, it is possible to establish a relationship between the change in chronobiological cycles and the prevalence of poor sleep, in order to develop health diseases.